La Inteligencia Espacial en el desarrollo del Aprendizaje Significativo en los niños y niñas de 4 a 5 años en la Unidad Educativa Manuel de Echeandía del cantón Guaranda en el periodo lectivo 2017-2018 - Torres Valencia, Lincoln Josè Adolfo (2018)
The main objective of the following study is to develop and apply the didactic guide based on spatial intelligence for the development of meaningful learning in children from 4 to 5 years old in the Manuel de Echeandía Educational Unit of the Guaranda canton during the 2017- 2018 This helps children develop skills to recognize objects, imagine movements, displacements, spatial relationships, problem solving and how this influences to achieve meaningful learning that is nothing more than a long-term, reflective, critical learning , not rote. The current research is based on the methodology that according to the purpose is applied research, according to the place field research, according to the object of study experimental research, according to the source of bibliographic research, according to the method to be used inductively. Consequently the design of the research is experimental since the researcher applies the didactic guide of spatial intelligence, also the design is longitudinal because a study is carried out in two periods of time (pre and post) and the type of study applied is quantitative so which is the observation card that provides information from the direct observation of the development of meaningful learning of a finite population of 33 students, which is why it is not considered a sample because the population is small, in which after performing the descriptive statistics determine that the distribution of the data is not normal, therefore, the nonparametric statistical test is applied. Wilcoxon signs with a confidence level of 95% and a margin of error of 5%, subsequently a detailed analysis is made of each of the indicators established in the present investigation in which per limit determine that: The level of development of open work increased 0.77 out of 3, which represents 25.66%, the level of development of intrinsic motivation increased 0.99 out of 3, which represents 33%, the level of development of the creativity increased 1.00 out of 3, which represents 33.33%, the level of development of the conceptual map increased 1.32 out of 3, which represents 43.84%. Based on all the data mentioned above, it is determined that the didactic guide based on spatial intelligence influences the development of meaningful learning in children from 4 to 5 years of age in the Manuel de Echeandía Educational Unit of the Guaranda canton during the school year. 2017- 2018. Keywords: Space intelligence, Wilcoxon, creativity, meaningful learning, intrinsic motivation, longitudinal, the didactic guide.